Analysis of Reject for Black Tea Products Extract on Production Process - Nelfiyanti Nelfiyanti; Fatma Sari; A I Ramadhan (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2019)
Quality is a factor that determines the success of a product penetrate the market, in addition to other major factors such as price and service. Quality products will have great competitiveness and high quality level. Products produced from extracts of natural ingredients, one product is Black Tea extract. To maintain customer satisfaction, the company tries to emphasize the value of DPU that occurs. This study aims to analyze the defect reject from the production of Black Tea Extract for a year using SIPOC diagram (Supplier Input Process Output) and Pareto diagram. Result of research is total production during that period equal to 358 batch x 300 Kg = 107400 kg, total reject of 78 batch x 300 kg = 23400 kg, with total reject for Black tea extract 21,79%. Can be known in the process of Black Tea extract reject largest in reject brix out of spec for 93.67% and Reject Tannin out of spec 6.33%. So it can be concluded that the dominant reject of the production process for black tea extract products is reject brix out of spec.